A game analysis on the rally-point system in badminton singles game observed on score efflux and how to play the game - Watanabe, H.; Takahashi, K. (Japanese Journal of Elite Sports Support, 2009)
Diversification of the rule in badminton was change to the rally point system, and which will cause many diversification. It is important to consider score development, and the percentage of victories, the characteristic of a game and a player's consciousness about singles to grasp the characteristic of a new rule. The average-time of game, the number of stroke, whose number of rallies, etc. increased when ability became near and it was the same also as for the man and the woman. Moreover, a winner's SSP (the score when it has a right of service.) decreased and a loser's SSP increased. The relationship between a point lead and the percentage of victories is. The lead side was made to won by high odds. Moreover, which side with much consecutive point won by high odds. It will considered that both consciousness has also influenced, the led side and the another side. The above result is . which may become an indicator for training planning and tactics planning.